Formic Acid Derivatives as Practical Carbon Monoxide Surrogates for Metal-Catalyzed Carbonylation Reactions - Konishi, Hideyuki; Manabe, Kei (Synlett, 2014)
This account describes our findings on formic acid derivatives as practical carbon monoxide (CO) surrogates in synthetic organic chemistry. Among the known CO surrogates, formic acid derivatives are advantageous in terms of their good availability, stability, and ease of handling. We adopted two approaches to expand the synthetic utility of formic acid derivatives. One is the use of formic acid esters for reactions with alkenes based on the finding that substituted imidazoles can function as the ligands in ruthenium-catalyzed hydroesterifications of alkenes. The other approach involves the use of formic acid derivatives for reactions with (hetero)aryl or alkenyl halides based on the finding that phenyl formate undergoes decomposition to give CO and phenol by simply reacting with a weak base such as triethylamine. In addition to phenyl formate, electrophilic formic acid derivatives such as 2,4,6-trichlorophenyl formate and N-formylsaccharin were found to be stable on storage, but highly reactive, even under ambient reaction conditions, functioning as CO-generating compounds. The in situ generated CO can be incorporated efficiently into products under metal catalysis, thus providing a novel carbonylation. Notably, the carbonylation process did not require the use of external gaseous CO, thus significantly enhancing the safety and practicality of the approach.1 Introduction2 Ruthenium-Catalyzed Hydroesterification3 Palladium-Catalyzed Aryloxycarbonylation3.1 Decomposition of Phenyl Formate under Weakly Basic Conditions3.2 Aryloxycarbonylation Using Phenyl Formate3.3 Room-Temperature Aryloxycarbonylation Using 2,4,6-Trichlorophenyl Formate4 Reductive Carbonylation Using N-Formylsaccharin5 Fluorocarbonylation Using N-Formylsaccharin6 Conclusion
Keywords: metal catalysis; hydroesterification; carbonylation; formic acid derivatives; carbon monoxide surrogates